Scientific Collaboration on the Internet 2008
DOI: 10.7551/mitpress/9780262151207.003.0005
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of Remote Scientific Collaboration

Abstract: In the past fifteen years, a great deal has been learned about the particular challenges of distant collaboration. Overall, we have learned that even when advanced technologies are available, distance still matters (Olson and Olson 2000). In addition, a recent seminal study of sixty-two projects sponsored by the National Science Foundation (NSF) showed that the major indicator of lower success was the number of institutions involved (Cummings and Kiesler 2005; chapter 5, this volume). The greater the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 28 publications
4
66
0
1
Order By: Relevance
“…Clark and Brennan (1991) have identified that lack of common ground (e.g., mutual knowledge) and trust can hinder collaboration. Olson et al (2008) have corroborated these findings in their investigations with collaboratory interactions among scientists, further emphasizing the role of history and shared vocabulary among collaborators as an essential facet of successful virtual collaboration. Olson et al (2008) note in their collaboratory studies that providing support for processes of management, planning, and decision-making is important.…”
Section: Related Worksupporting
confidence: 62%
See 3 more Smart Citations
“…Clark and Brennan (1991) have identified that lack of common ground (e.g., mutual knowledge) and trust can hinder collaboration. Olson et al (2008) have corroborated these findings in their investigations with collaboratory interactions among scientists, further emphasizing the role of history and shared vocabulary among collaborators as an essential facet of successful virtual collaboration. Olson et al (2008) note in their collaboratory studies that providing support for processes of management, planning, and decision-making is important.…”
Section: Related Worksupporting
confidence: 62%
“…Olson et al (2008) have corroborated these findings in their investigations with collaboratory interactions among scientists, further emphasizing the role of history and shared vocabulary among collaborators as an essential facet of successful virtual collaboration. Olson et al (2008) note in their collaboratory studies that providing support for processes of management, planning, and decision-making is important. When there are multiple institutions involved and/or different departments (disciplines) within the same university, it is important to know who is serving in what role.…”
Section: Related Worksupporting
confidence: 62%
See 2 more Smart Citations
“…www.myexperiment.org). This distributed effort brings the niche, microexpertise as well as microcontributions and microcollaboration (Olson et al 2008) in the mainstream research resulting in increased efficiency and faster solutions to complex problems (ATLAS particle detector project 19 in CERN engaged 2800 scientific authors including 1850 with a PhD and 1200 technicians from 169 institutions from 37 countries, also thousands of industrial relations were built -Hoffman, 2009). Nevertheless, the growth of open collaboration is sketchy and its usage is relatively low.…”
Section: Open Distributed Collaborationmentioning
confidence: 99%